The prevalence of Anaemia among men and women in rural Bangladesh - Hyder, SM Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
Anaemia is a major public health problem in many developing countries including Bangladesh. Iron deficiency is known to be the commonest cause of anaemia resulting from inadequate iron intake, reduced bio-availability of ingested iron, defective mobilisation of iron reserves, increased needs for iron under certain physiological and pathological conditions and so on. This study aimed at investigating the prevalence of anaemia among rural men and women. The survey was conducted in March 1996 in 12 villages of Mymensingh District located about 100 km north of Dhaka city. Eighty four adult men and 184 adult women aged 15-48 years and 22 adolescent boys and 44 adolescent girls aged 11-14 years were randomly selected. Information was obtained on haemoglobin concentration, parasitic infestation, literacy and on other household socioeconomic parametres. It was revealed from the study that mean haemoglobin concentration of the study population was 114 gIL, and about 69% adult men, 71% adult women, 68% adolescent boys and 64% adolescent girls were suffering from anaemia according to the WHO criteria. This study suggests that anaemia is highly prevalent in the rural communities of Bangladesh which victimises both men and women equally. There is an urgent need to conduct further studies to confirm if male and female are equally anaemic to provide important feedback to the existing anaemia control programmes in the country.